Citizen concerns about and responses to the water crisis in a high-income suburb in Cape Town, South Africa - Marcus, Thaakirah; Spocter, Manfred (Modern Geográfia)
Water is the lifeblood of human and animal existence. The growth of urban populations places increasing pressure on governments to capture, store, and deliver potable water to city residents. Human-induced changes to the Earth’s climate have led to unpredictable rainfall patterns. In Cape Town, South Africa, three consecutive years of below-average winter rainfall (beginning in 2015) severely tested the city’s ability to provide potable water to its citizens. The city’s taps were on the brink of running dry, prompting residents to implement measures to reduce water consumption. Grounded in the theoretical framework of the theory of planned behaviour, this paper investigates household water circumstances, residents’ concerns, and their responses to the drought in the high-income suburb of Newlands. Semi-structured interviews were conducted with 30 household heads. A content analysis of the interview data revealed four key themes: concern about the water shortage, concern for fellow citizens, dissatisfaction with the City’s crisis management, and household responses to the drought. An exploration of these themes offers valuable citizen-based insights that may inform the management of future water crises and support citizen-led water management strategies.